Principles for the socially responsible use of conservation monitoring technology and data. Issue 5 (3rd March 2021) - Sandbrook, Chris; Clark, Douglas; Toivonen, Tuuli; Simlai, Trishant; O'Donnell, Stephanie; Cobbe, Jennifer; Adams, William
Abstract: Wildlife conservation and research benefits enormously from automated and interconnected monitoring tools. Some of these tools, such as drones, remote cameras, and social media, can collect data on humans, either accidentally or deliberately. They can therefore be thought of as conservation surveillance technologies (CSTs). There is increasing evidence that CSTs, and the data they yield, can have both positive and negative impacts on people, raising ethical questions about how to use them responsibly. CST use may accelerate because of the COVID‐19 pandemic, adding urgency to addressing these ethical challenges. We propose a provisional set of principles for the responsible use of such tools and their data: (a) recognize and acknowledge CSTs can have social impacts; (b) deploy CSTs based on necessity and proportionality relative to the conservation problem; (c) evaluate all potential impacts of CSTs on people; (d) engage with and seek consent from people who may be observed and/or affected by CSTs; (e) build transparency and accountability into CST use; (f) respect peoples' rights and vulnerabilities; and (g) protect data in order to safeguard privacy. These principles require testing and could conceivably benefit conservation efforts, especially through inclusion of people likely to be affected by CSTs. Abstract : Wildlife conservation benefits enormously from automated and interconnected monitoring tools, some of which can collect data on humans; either accidentally or deliberately. There is increasing evidence that these Conservation Surveillance Technologies and the data they yield can have both positive and negative impacts on people, raising ethical questions about how to use them responsibly. We propose a provisional set of principles for the socially responsible use of such tools and their data.